Zingiber arunachalensis (Zingiberaceae): a new species from northeastern India - Joe, Alfred; Jayakrishnan, Thachat; Hareesh, Vadakkoot Sankaran; Sabu, Mamiyil (Phytotaxa, 2017)
In 2015, during a floristic expedition in northeastern India, a population of an unusual Zingiber Miller (1754: 525) was found near Durga Mandir, between Bomdilla and Balukpong, in West Kameng District, Arunachal Pradesh. At a first glance the species clearly belongs to section Cryptanthium Horaninow (1862: 27) in having a procumbent peduncle. Detailed studies revealed that it does not match any of the known species of Indian Zingiber, hence it is described here as new. Plants of this population are morphologically similar to Z. bipinianum Roy et al. (2015: 298) and Z. mizoramensis Kumar et al. (2015: 81), but detailed studies of the types and protologues confirm the novelty of this species. We also consulted relevant literature discussing Indian Zingiberaceae, which further confirms that this is a new species (e.g. Bai et al. 2015, Baker 1892, Leong-Škorničková et al. 2015, Kishor & Leong-Škorničková 2013, Kumar et al. 2013, 2015, Mood & Theilade 2002, Roscoe 1828, Sabu 2003, 2006, Sabu et al. 2009, 2013b, Talukdar et al. 2015, Thongam & Konsam 2014, Thongam et al. 2013, Triboun et al. 2014, Tripathi & Singh 2006, Wu & Larsen 2000).